Improving Teacher Performance in Developing Teaching Materials Through Academic Supervision as an Effort to Improve Academic Quality in Schools - Mahsun Alwa'id (Indonesian Journal of Instructional Media and Model, 2021)
An important problem that is often faced by teachers in learning activities is choosing or determining appropriate learning materials or teaching materials in order to help students achieve competence. This is due to the fact that in the curriculum or syllabus, teaching materials are only written in outline in the form of "subject material". It is the teacher's job to describe the subject matter so that it becomes a complete teaching material. In addition, how to use teaching materials is also a problem. The intended use is how to teach it from the teacher's point of view, and how to learn it from the student's point of view. The purpose of this school action research (PTS) is to find out the extent to which the coaching of the Madrasah Principal improves the performance of teachers in choosing teaching materials. In this school action research (PTS), it was carried out in 3 cycles, from the results of the actions taken it was proven to be able to improve teacher performance by achieving ideal standards. From 64.47% in the first cycle, it could increase to 74.59% in the second cycle, and the second cycle. to III 83.29%. The results of this action research indicate that coaching through the academic supervision of the Madrasah Head can improve teacher performance in choosing teaching materials at MAN 1 Semarang, Semarang Regency.